Exploring Counseling-Based Pedagogy in EFL Classrooms: Perceived Values of English Language Teachers in Nepal - Joshi, Dev Ram (Far Western Journal of Education, 2025)
Nepalese students learn Japanese, Korean, and other languages within a short period of time or within twelve months but they do not develop the proficiency level in English as t equal to those languages despite studying English for twelve years. Why is it happening? Where is the gap? What should be done to make English language learners more aware about learning English? These burning issues forced me to rethink the language pedagogy that we are applying in the school settings. In the process of professional practices, I developed an insight that language pedagogy should embrace critical awareness in language learning and make teacher and learners supportive and respectful to each other. Therefore, I have explored the perspectives of English teachers on Counseling-Based Pedagogy (CPB) under the framework of qualitative case study research design collecting data with the help of document study, Google forms, and telephone conversations. I found positive attitudes and strong beliefs of my participants on this pedagogy which encouraged me to investigate further on it because their case examples of improving English proficiency along with learners’ personal growth indicate that this pedagogy can contribute to ELT. The implications of this study are useful for English teachers and researchers to experiment how supportive and respectful classroom atmosphere, empathetic communication, and critical awareness enhance English language teaching and learning in Nepalese context.